Toward heterologous production of monoterpene indole alkaloids in a microbial system / Dr Roslinah Mohamad Hussain - Mohamad Hussain, Roslinah (Faculty of Heath Sciences, 2013)
Plant secondary metabolites such as alkaloids, terpenoids and polyketides and others have immense medicinal, pharmaceutical and agricultural applications. Many are sought for their therapeutic potentials against various cancers and tumors. In plants, secondary metabolites are products of complex biosynthetic pathways that take years to produce and even then, at miniscule levels. Recognising these constraints, bioengineering technologies attempt to yield productions of these valuable compounds in robust systems such as in bacteria or yeast. This project attempts to reconstruct the biosynthetic pathway VIS bioengineering and molecular methods towards production of a monoterpene alkaloid that is normally produced in plants in a microbial system such as Saccharomyces cerevisiae. The undertaken project represents the initial pathway, in a myriad of biosynthetic pathways leading towards production of Vinblastine, an expensive commercialized antitumor drug that is currently used. The following outlines a summary of the procedural experimental work that I performed in attempt to obtain the desired outcome.